Effects of temporarily altering alfalfa levels in high-concentrate diets on subacute acidosis - Healy, B.J.; Brandt, Robert T., Jr. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Four ruminally cannulated crossbred steers (882 lb) were used to investigate the effects of temporarily altering the levels of alfalfa in a high-concentrate diet on ruminal characteristics during a bout of experimentally induced subacute acidosis. A diet based on dry rolled corn with 8% alfalfa hay was fed before and after a 2-day challenge phase when steers were forced to consume 2.5% of their body weight in 90 minutes each day after a prior 24-hour fast. During the challenge phase, steers were fed diets containing 5, 8, 11, or 14% alfalfa. Feed intake quickly recovered for steers fed all but the 5% alfalfa diet, with a tendency for a linear (P<.11) decline in feed intake as alfalfa was decreased in the challenge diet. The intensity and duration of the pH drop were increased as the level of alfalfa decreased. Mean pH decreased, total VFA concentration increased, and the ratio of acetate:propionate decreased linearly (P<.06) as level of alfalfa decreased. Because the ruminal parameters measured for the 8% and 11% alfalfa diets were similar, the data suggest that temporarily increasing the basal diet to more than 11% alfalfa is necessary to mitigate the effects of a forced disruption in feed intake. Increasing the level of alfalfa hay from 8 to 14% of diet dry matter increased fluid dilution rate, lowered time that ruminal pH was below 5.5, and resulted in higher mean ruminal pH in steers with experimentally induced acidosis.
Keywords: Beef; Steers; Acidosis; Roughage level; Alfalfa